Vitamin D supplements in sports: a long run for a short jump - Eichner, E. R. (Current Sports Medicine Reports, 2023)
Vitamin D supplements (VDS) in sports - and in clinical medicine in general - have been in vogue for nearly two decades. After hundreds of studies , their allure is beginning to fade, and rightly so. Let me explain. I will start with sports, then go to general clinical medicine, and then close with sports.